Solubility Enhancement of Cefdinir using different Pharmaceutical Approaches for Enhancement of the Drug Performance - Ghaidaa S. Hameed; Dalya Basil Hanna; Naama, Naamaa (Iraqi Journal of Pharmaceutical Sciences, 2025)
Cefdinir (CEF) is classified as a third-generation cephalosporin within class IV of the Biopharmaceutical Classification System (BCS). Consequently, it exhibits limited solubility in water, which might diminished oral bioavailability. This study aimed to compare CEF in different engineered product. Specifically, the CEF was physically mixed with co-former and then processed using different methods such as co-amorphous system formation with curcumin, binary solid dispersion with polyvinylpyrrolidone k30 (PVP) and with soluplus and ternary solid dispersion with curcumin and PVP using solvent evaporation method. The products were subjected to characterization using Differential Scanning Calorimetry (DSC), Powder X-ray Diffractometry (PXRD), and Fourier Transform Infrared Spectroscopy (FTIR). Additionally, dissolution and antibacterial activity tests were performed on these systems. The findings indicate a decrease in crystallinity for both curcumin and soluplus binary systems. Conversely, in the case of CEF with PVP binary SD and ternary SD with curcumin, the results demonstrate the entire creation of an amorphous system, resulting in improved release and antibacterial properties compared to the pure drug. The presence of PVP in the solvent evaporated product in both binary and ternary product produce a miscible mix which might correlated to this totally amorphous solid dispersed system.